Prenatal exposure to triclosan assessed in multiple urine samples and placental DNA methylation - Paulina Jedynak; Lucile Broséus; Jörg Tost; Florence Busato; Stephan Gabet; Cathrine Thomsen; Amrit K. Sakhi; Isabelle Pin; Rémy Slama; Johanna Lepeule; Claire Philippat (Environmental Pollution, 2023)

Prenatal exposure to synthetic phenols and phthalates and child respiratory health from 2 to 36 months of life - Ophélie Coiffier; Sarah Lyon-Caen; Anne Boudier; Joane Quentin; Yoann Gioria; Isabelle Pin; Sam Bayat; Cathrine Thomsen; Amrit K. Sakhi; Azemira Sabaredzovic; Rémy Slama; Claire Philippat; et al. (Environmental Pollution, 2023)

Pre-natal exposure to NO2 and PM2.5 and newborn lung function: An approach based on repeated personal exposure measurements - Johanna Lepeule; Isabelle Pin; Anne Boudier; Joane Quentin; Sarah Lyon-Caen; Karine Supernant; Emie Seyve; Ryan Chartier; Remy Slama; Valérie Siroux (Environmental Research, 2023)

Beyond the boom-bust cycle: An interdisciplinary framework for analysing crop booms - Jean-Christophe Castella; Juliet Lu; Cecilie Friis; Thilde Bech Bruun; Robert Cole; Victoria Junquera; Miles Kenney-Lazar; Sango Mahanty; Christine Ornetsmüller; Pin Pravalprukskul; Isabelle Vagneron (Global Environmental Change, 2023)

Toward the Standardization of Mycological Examination of Sputum Samples in Cystic Fibrosis: Results from a French Multicenter Prospective Study - Noémie Coron; Marc Pihet; Emilie Fréalle; Yolande Lemeille; Claudine Pinel; Hervé Pelloux; Gilles Gargala; Loic Favennec; Isabelle Accoceberry; Isabelle Durand-Joly; Frédéric Dalle; Frédéric Huet; et al. (Mycopathologia, 2018)

Diversifying mechanisms in the on‐farm evolution of crop mixtures - Mathieu Thomas; Stéphanie Thépot; Nathalie Galic; Sophie Jouanne‐Pin; Carine Remoué; Isabelle Goldringer (Molecular Ecology, 2015)
While modern agriculture relies on genetic homogeneity, diversifying practices associated with seed exchange and seed recycling may allow crops to adapt to their environment. This socio‐genetic model is an original experimental evolution design referred to as on‐farm dynamic management of crop diversity. Investigating such model can help in understanding how evolutionary mechanisms shape crop diversity submitted to diverse agro‐environments. We studied a French farmer‐led initiative where a mixture of four wheat landraces called ‘Mélange de Touselles’ (MDT) was created and circulated within a farmers' network. The 15 sampled MDT subpopulations were simultaneously submitted to diverse environments (e.g. altitude, rainfall) and diverse farmers' practices (e.g. field size, sowing and harvesting date). Twenty‐one space‐time samples of 80 individuals each were genotyped using 17 microsatellite markers and characterized for their heading date in a ‘common‐garden’ experiment. Gene polymorphism was studied using four markers located in earliness genes. An original network‐based approach was developed to depict the particular and complex genetic structure of the landraces composing the mixture. Rapid differentiation among populations within the mixture was detected, larger at the phenotypic and gene levels than at the neutral genetic level, indicating potential divergent selection. We identified two interacting selection processes: variation in the mixture component frequencies, and evolution of within‐variety diversity, that shaped the standing variability available within the mixture. These results confirmed that diversifying practices and environments maintain genetic diversity and allow for crop evolution in the context of global change. Including concrete measurements of farmers' practices is critical to disentangle crop evolution processes.

Evidence for linkage of a new region (11p14) to eczema and allergic diseases - Michel Guilloud-Bataille; Emmanuelle Bouzigon; Isabella Annesi-Maesano; Jean Bousquet; Denis Charpin; Frédéric Gormand; Joëlle Hochez; Jocelyne Just; Arnaud Lemainque; Nicole Le Moual; Régis Matran; Françoise Neukirch; et al. (Human Genetics, 2008)

Evidence for a pleiotropic QTL on chromosome 5q13 influencing both time to asthma onset and asthma score in French EGEA families - Emmanuelle Bouzigon; Ayse Ulgen; Marie-Hélène Dizier; Valérie Siroux; Mark Lathrop; Francine Kauffmann; Isabelle Pin; Florence Demenais (Human Genetics, 2007)